Handbook of Retinal Screening in Diabetes : Diagnosis and Management. - Taylor, Roy (John Wiley & Sons, 2012)
Beginning with chapters summarizing the basics of diabetic retinopathy, this updated volume outlines the need for screening, how to screen safely and correctly, and the normal condition of the retina without diabetic retinopathy, all using excellent line and halftone illustrations. The core focus then moves on to examining each different form of retinopathy, all supported by outstanding color retinal photographs illustrating the appearance of the retina at various stages of retinopathy, plus an analysis on the best treatment for each stage. The book ends with chapters providing self-assessment.